Silvopastoralism and the shaping of forest patches in the Atacama Desert during the Formative Period (ca. 3000–1500 years BP). (December 2022) - McRostie, Virginia; Babot, Pilar; Calás, Elisa; Gayó, Eugenia; Gallardo, Francisco; Godoy-Aguirre, Carolina; Labarca, Rafael; Latorre, Claudio; Núñez, Lautaro; Ojeda, Karla; Santoro, Calogero M; Valenzuela, Daniela
During the Formative period by the Late-Holocene (ca. 3000–1500 BP), semi-sedentary and sedentary human occupations had emerged in the oases, salares, and riverine systems in the central depression (2400–1000 masl) of the Atacama Desert, northern Chile (19–25°S). This hyperarid core was marginally occupied during the post-Pleistocene and middle Holocene droughts. Settlement on these lower belts was accompanied by a rise in humidity, the introduction of Andean crops, flourishment of Prosopis spp. (algarrobo) forests, and increasing integration of domestic camelid caravans. Here, we explore lowland husbandry within risk-spreading strategies, focusing on silvopastoralism and endozoochory between camelids and algarrobos. Analysis of camelid coprolites from seven archeological sites located in the Pampa del Tamarugal, Loa River, and Salar de Atacama found intense grinding from camelid chewing and indicated a ruminal digestive system. Abundant macro and microremains in the form of tissues, phytoliths, crystals, cell structures, and others, were identified as Prosopis, Atriplex, Schoenoplectus, Distichlis, and Phragmites . We conclude that camelids were foraging for Prosopis, although the rather low number of entire seeds preserved in the coprolites leads us to think that these herbivores might not have been the main vectors for the spread and germination of algarrobos. More samples and interdisciplinary studies are needed to comprehend the complex socioecological web in the shaping of these forests and the management of the Atacama Desert landscapes.